Feasibility and Efficacy Study of Spices in Meat Preservation - Banik, A; Abony, M; Ahamed, Z; Shishir, MA (Stamford Journal of Microbiology, 2022)
The systematic application of spices as natural food preservatives could be the key to withstanding different food-borne diseases and the frequent use of antibiotics could be reduced thereby. Eight indigenous spices were tested against six food-borne pathogens. The spice extracts were prepared by drying, grinding, and soaking into 95% ethanol and the antibacterial activity was evaluated by the well-diffusion method. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by the broth dilution method. The feasibility of spices as natural meat preservatives was then assessed through the application. The ethanol extracts of the spices potentially inhibited the test organisms. Maximum activity (zone of inhibition- ZOI) was recorded for garlic (17.83±2.48 mm) followed by black pepper (17±8.9 mm), black cumin (15.83±10.87 mm), and ginger (15.16±7.68 mm). For pathogens, the most susceptible was B. cereus (19.57±8.05 mm) followed by Acinetobacter sp. (18.14±1.34 mm), E. coli (16.28±1.88 mm), S. aureus (14.28±9.91 mm), V. cholerae (10.85±7.94 mm) and Salmonella enterica ser. Typhi (6.85±8.55 mm). Garlic exhibited the most effective and consistent inhibitory activity whereas black cumin exhibited the highest activity against B. cereus (34 mm). These results were highly comparable to the commercial antibiotics, e.g. Meropenem (28 mm). Against the Salmonella spp., ginger, cumin, and garlic demonstrated moderate inhibition (16 mm) whereas complete resistance was observed against other spices. The lowest MIC and MBC were recorded for black cumin against B. cereus (32 mg/ml and 64 mg/ml, respectively). But garlic was found to be the best candidate due to its lowest mean MIC (85.33±33 mg/ml), and MBC (170.66±66 mg/ml). Black cumin, garlic, and black pepper were efficient in reducing the total viable count of meat at 72 hours and hence could be developed as natural food preservatives. Stamford Journal of Microbiology, Vol.12 (1) 2022: 31-36